Critical appraisal of bepotastine in the treatment of ocular itching associated with allergic conjunctivitis - Jeremy B Wingard (Dove Medical Press, 2011)
Jeremy B Wingard, Francis S MahUPMC Eye Center, Department of Ophthalmology, University of Pittsburgh School of Medicine, Pittsburgh, PA, USAAbstract: Bepotastine besilate 1.5% solution is an H1-antihistamine recently approved by the Food and Drug Administration for the topical treatment of ocular itching associated with allergic conjunctivitis. Several clinical studies have demonstrated its safety as well as its efficacy versus placebo. This review finds that bepotastine besilate 1.5% solution is a suitable alternative to other agents within the class of H1-antihistamines, but there are no clinical trial data to suggest that it holds any specific advantages over other agents.Keywords: allergic conjunctivitis, antihistamine, ocular itching